ONTOLOGICAL AND EPISTEOLOGICAL VIEWS OF SAYID SHARIF JURJANI (Scientific journal of the Fergana State University, 2025)
This article studies the ontological and epistemological views of Sayyid Sharif Jurjani and substantiates them from a philosophical point of view. The concept of the world is based, first of all, on the reflection of the universe and the space in which its activities take place. Philosophical views on being are deeply analyzed, and Jurjani's ideas on being and epistemology are scientifically revealed and analyzed.